RELIGIOUS ANTHROPOCENTRISM: The Discourse of Islamic Psychology among Indonesian Muslim Intellectuals (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
Ideas in psychology are often criticized as being dominated by the spirit and the model of secular and liberal Western thinking. They are frequently deemed to bring bias when applied to analyze the psychological problems of human beings in the context of other cultures, especially in the context of Islamic culture. This paper investigates Indonesian Muslim scientists’ offer of an alternative of grand theory in psychology formulated from a more balanced paradigm called religious anthropocentric psychology. Indonesian Muslim scientists develop this paradigm as an attempt to construct spiritual-religious psychology or Islamic psychology. The paper describes an increasing awareness among those Muslim scientists to develop theories of humanistic psychology with spiritual and religious values. This kind of psychological theory seems to be the basis for so-called Islamic psychology. Furthermore, in addition to its reference toward the anthropocentric paradigm, this kind of psychology also refers to the religious-Islamic values, theo-centric or God-centric.